2001
DOI: 10.1002/bit.10144
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin production from CHO cells grown by continuous culture in a fluidized‐bed bioreactor

Abstract: A Chinese hamster ovary (CHO) cell line that expresses human erythropoietin (huEPO) was in a 2-L Cytopilot fluidized-bed bioreactor with 400 mL macroporous Cytoline-1 microcarriers and a variable perfusion rate of serum-free and protein-free medium for 48 days. The cell density increased to a maximum of 23 x 10(6) cells/mL, beads on day 27. The EPO concentration increased to 600 U/mL during the early part of the culture period (on day 24) and increased further to 980 U/mL following the addition of a higher con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 46 publications
1
49
1
1
Order By: Relevance
“…During the development of a perfusion process producing EPO, it was also observed that a constant perfusion rate allowed the system to approach steady state, in which the concentration of the main components were maintained at a constant level (Wang et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the development of a perfusion process producing EPO, it was also observed that a constant perfusion rate allowed the system to approach steady state, in which the concentration of the main components were maintained at a constant level (Wang et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In the course of reducing the perfusion rate, several studies were conducted where the concentration of glucose (Dowd et al 2001;Wang et al 2002) is used as an indicator of other nutrients level in the feed medium in order to operate the bioreactor at a low perfusion rate without accumulating in the culture high levels of toxic byproducts such as lactate and ammonia Sugiura and Kakuzaki 1998). Modification of culture parameters such as pH or temperature (Chuppa et al 1997) is also a common strategy to optimize culture conditions and reduce medium perfusion needs.…”
Section: Introductionmentioning
confidence: 99%
“…Butyrate treatment in CHO cells affects cellular processes such as cytoskeleton reorganization, protein transport, nucleosome assembly, nucleotide metabolism, glycosylation, protein folding, oxidative stress responses, lipid metabolism, cholesterol biosynthesis, glycolysis, cell cycle progression, and apoptosis (Yee et al 2008;De Leon et al 2007). Butyrate has been used in cell engineering strategies, and butyrate treatment in CHO cells often increases recombinant protein expression (Chun et al 2003;De Leon et al 2007;Hendrick et al 2001;Kim and Lee 2000;Chotigeat et al 1994;Mimura et al 2001;Wang et al 2002;Jiang and Sharfstein 2008). The current work explores the effect of butyrate on glycosaminoglycan (GAG) profiles in recombinant CHO cells in our efforts to produce a bioengineered heparin (HP).…”
Section: Butyrate Work As a Histone Deacetylase Inhibitor Andmentioning
confidence: 99%
“…Sodium butyrate (CH 3 CH 2 CH 2 CO 2 -) is a histone deacetylase inhibitor that modulates gene expression of cellular processes, particularly transgene expression in Chinese hamster ovary (CHO) cells (Chotigeat et al 1994;Chun et al 2003;De Leon et al 2007;Hendrick et al 2001;Jiang and Sharfstein 2008;Kim and Lee 2000;Mimura et al 2001;Wang et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Sodium butyrate는 가장 널리 사용되는 SME 중 하나 로, 동물세포배양을 이용하여 tPA [9], α 1 -antitrypsin [10], hEPO [11], scu-PA [12], immunoglobulin [13] Fig. 3(a) .…”
Section: 서론unclassified